Adrenal gland primary tuberculosis: report of two cases - Coras, Natalia (2013)
Tuberculosis is highly prevalent and is still currently the leading cause of adrenal insufficiency in many areas of the world. Clinically this disease remains asymptomatic during early stages, but due to adrenal function loss symptoms become insidious and gradual, mostly unspecific. We report two cases of female patients with clinical symptoms of chronic bilateral primary adrenal insufficiency with active tuberculosis infection by histopathology.